2019
DOI: 10.24271/garmian.196356
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Self-Management and Level of Asthma Control among Adult Asthmatic Patients Attending Kalar General Hospital

Abstract: Background: As asthma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“… 14 Another study illustrated that 62.7% of asthmatics have poor, 12% have good and only 25.3% possess an adequate knowledge of their condition. 15 Similar studies showed that although the patients have a positive attitude towards the disease, their specific disease knowledge was low. 16 17 In our study, the proportion of patients (16.7%) who correctly answered more than 50% of the questions was greater than that reported by Al et al, 13 (4%) but similar to that reported by Nguyen et al (16.5%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 14 Another study illustrated that 62.7% of asthmatics have poor, 12% have good and only 25.3% possess an adequate knowledge of their condition. 15 Similar studies showed that although the patients have a positive attitude towards the disease, their specific disease knowledge was low. 16 17 In our study, the proportion of patients (16.7%) who correctly answered more than 50% of the questions was greater than that reported by Al et al, 13 (4%) but similar to that reported by Nguyen et al (16.5%).…”
Section: Discussionmentioning
confidence: 94%
“…A multicentre study in China reported a low level of disease awareness among the parents of asthmatic children 14. Another study illustrated that 62.7% of asthmatics have poor, 12% have good and only 25.3% possess an adequate knowledge of their condition 15. Similar studies showed that although the patients have a positive attitude towards the disease, their specific disease knowledge was low 16 17.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally Abbas et al (2019) (36) , reported that the lower percentage of the participants had good knowledge pre-program and improved after program. Similarly with Elbanna, et al (2017) (37) who reported that most participants had good knowledge scores after the program application with a statistically significant difference in the total score of knowledge pre and post the program.…”
Section: Discussionmentioning
confidence: 99%